Immunogenicity of Renal Microvascular Endothelial Cells From Genetically Modified Pigs. Issue 3 (March 2016) - Wang, Zheng-Yu; Li, Ping; Butler, James R.; Blankenship, Ross L.; Downey, Susan M.; Montgomery, Jessica B.; Nagai, Shunji; Estrada, Jose L.; Tector, Matthew F.; Tector, A. Joseph
Abstract : Background: Disrupting the porcine GGTA1 and CMAH genes [double knockout (DKO)] that produce the gal-α(1, 3)-gal and N-glycolylneuraminic acid xenoantigens reduces human antibody binding to porcine peripheral blood mononuclear cells. It is important to examine rejection pathways at an organ-specific level. The object of this study is to evaluate the human preformed antibody reactivity against DKO renal microvascular endothelial cells (RMEC) in vitro. Methods: Characteristics of DKO RMEC were analyzed using flow cytometry. Human IgG/M binding to primary RMEC, immortalized RMEC (iRMEC), and iRMEC-deficient in B4GALNT2 genes were examined using flow cytometric crossmatch assay. Results: Porcine RMEC expressed gal-α(1, 3)-gal, N-glycolylneuraminic acid, and Dolichos biflorus agglutinin glycans recognized by human preexisting antibodies in humans. Antigenicity of DKO RMEC was lower than GGTA1 KO RMEC. The disruption of B4GALNT2 gene in DKO iRMEC further reduced human IgG/IgM binding. Conclusions: Silencing the porcine GGTA1, CMAH, and B4GALNT2 genes is an effective strategy to reduce human preformed antibody binding to RMEC. Porcine RMEC will be a useful reagent for the further study of xenoimmunology. Abstract : The authors evaluate the human preformed antibody reactivity against DKO renal microvascular endothelial (RMEC) cells in vitro. Silencing the porcine GGTA1, CMAH, and B4GALNT2 genes may effectively reduce the human preformed antibody binding to RMEC.